An assessment of the training needs of the library group in the National Library a projected human resources development plan - Macaspac, Gracia A.; Faderon, Rosalie B.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
This study attempts to identify the perceived training needs of The National Library group, their educational qualifications and the actual duties and responsibilities they perform so as to come up with a human resource development program for them.
The survey method was used in this study. The questionnaires were distributed to the 90 respondents assigned to the nine divisions of The National Library. Eighty-two of these were returned and were 100 percent usable.
The findings of this study are : 1) The library group is dominated by females, majority of whom belong to the group of 26-30, 36-40 and 31-35 years; 2) More than half of the library group are holders of the Bachelor of Science in Education degree: three finished their degrees in Library Science; others are undergraduates, and the rest are graduates of short-term courses; 3) Twenty-one have earned units in graduate courses in Library Science while eight have completed all the academic requirements in the graduate studies program; 4) Majority of the respondents possess skills like typing, indexing and abstracting and cataloging and classification; 5) Nine were recipients of fellowships and/or scholarships, eleven of meritorious awards from different institutions; 6) Twenty-six were once members of library associations but not always, 56 are non-members; 7) Seventy-two have attended training programs while 10 did not, 65 thought theses were relevant to the tasks they perform, seven felt that there were not; 8) Majority are assigned to the three divisions which maintain separate reading areas: Filipiniana and Asia, Reference and the Public Documents Division; 9) Majority have been in The National Library for 1-5 years; 7 for more than 31 years, 55 have been holding on to their positions for 1-5 years; 10) Salary increase and/or promotion is the number one motivating factor according to majority of the respondents; 11) Fifty-eight have signified to transfer to another institution to search for greener pasture and to advance while 24 have signified to stay on; 12) All the respondents need further training on the technical aspects of librarianship and administration and supervision; 13) Fifty-three are satisfied in their present tasks while 29 are dissatisfied; and 14) Twenty respondents are 85-100 percent engaged in cataloging and classification, 21 in reference and bibliographic services, 18 in indexing periodicals.
Some of the recommendations of the study are: 1) A regular budget should be allotted for staff development so that training programs can be carried out at regular intervals; 2) A standing committee should be created to take charge of the implementation of the HRD program and to draw up plans for the library group of TNL who are interested in formal and informal continuing programs; 3) A system of selection of participants should be based on demonstrated needs and actual work performance of the staff; 4) The training needs of the library group identified in this study must be met through a continuing series of seminars, workshops, site visits and other related programs; 5) The library group should strive hard to acquire new knowledge, skills and competencies in the field through training programs offered by The National Library and other institutions and associations; 6) The National Library must continue to coordinate with other institutions which regularly conduct training programs here and abroad; and 7) A continuous evaluation of training programs offered must be conducted at the end of each program to serve as the basis for improving further the planning and implementation of training programs.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library education -- Manila -- Philippines; Philippines. National Library